2012
DOI: 10.3762/bjoc.8.93
|View full text |Cite
|
Sign up to set email alerts
|

An intramolecular inverse electron demand Diels–Alder approach to annulated α-carbolines

Abstract: SummaryIntramolecular inverse electron demand cycloadditions of isatin-derived 1,2,4-triazines with acetylenic dienophiles tethered by amidations or transesterifications proceed in excellent yields to produce lactam- or lactone-fused α-carbolines. Beginning with various isatins and alkynyl dienophiles, a pilot-scale library of eighty-eight α-carbolines was prepared by using this robust methodology for biological evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 99 publications
0
2
0
Order By: Relevance
“…Synder et al recently demonstrated a robust ihDA/rDA methodology to prepare a library (88 compounds) of lactam and lactone fused a-carbolines in which the average yield, determined by UPLC, was 94% (Scheme 20). 58 They took advantage of the convergent synthetic nature of this methodology to modify the five main diversification sites on the core, while using readily available or easily prepared starting materials. As could be predicted, the pericyclic reactions were helped by reducing the electron density of the triazine core.…”
Section: 24-triazinesmentioning
confidence: 99%
“…Synder et al recently demonstrated a robust ihDA/rDA methodology to prepare a library (88 compounds) of lactam and lactone fused a-carbolines in which the average yield, determined by UPLC, was 94% (Scheme 20). 58 They took advantage of the convergent synthetic nature of this methodology to modify the five main diversification sites on the core, while using readily available or easily prepared starting materials. As could be predicted, the pericyclic reactions were helped by reducing the electron density of the triazine core.…”
Section: 24-triazinesmentioning
confidence: 99%
“…Whereas the Synder group showed the importance of the triazine as a diene reaction partner in the DAR inv in 1,2,4-triazine studies [47][48][49] , the Boger group systematically investigated the 1,2,3-triazines 50,51 ; earlier, the group exhibited expertise in the research of the DAR inv azadiene chemistry in the field of the total synthesis of nature identical molecules 4,5,52 .…”
Section: Synthesis Of Triazine Componentsmentioning
confidence: 99%